2007
DOI: 10.1158/1055-9965.epi-06-0751
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Risk of Endometrial Cancer: A Population-Based Prospective Cohort Study

Abstract: Although there is accumulating evidence that hyperinsulinemia in the context of insulin resistance is associated with carcinogenesis, only one prospective study of endometrial cancer incidence, in relation to diabetes, addressed this issue and showed no significant positive association. No previous study has investigated whether physical activity can modify the association between diabetes and endometrial cancer. We examined the association between diabetes and incidence of endometrial cancer and the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
116
2
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 53 publications
9
116
2
9
Order By: Relevance
“…In a Swedish cohort study of 225 cases of endometrial cancer, the relative risk was 2.7 for diabetic women reporting low physical activity and 1.1 among those reporting high physical activity (Friberg et al, 2007). In an Italian case -control study, the association with diabetes was of similar magnitude in women with or without hypertension (Parazzini et al, 1999).…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…In a Swedish cohort study of 225 cases of endometrial cancer, the relative risk was 2.7 for diabetic women reporting low physical activity and 1.1 among those reporting high physical activity (Friberg et al, 2007). In an Italian case -control study, the association with diabetes was of similar magnitude in women with or without hypertension (Parazzini et al, 1999).…”
mentioning
confidence: 95%
“…Diabetes shows a supramultiplicative effect with body mass index, but not with physical activity or hypertension. An increased risk of endometrial cancer in diabetic women has often been reported (Parazzini et al, 1991(Parazzini et al, , 1999Brinton et al, 1992;La Vecchia et al, 1994;Shoff and Newcomb, 1998;Salazar-Martinez et al, 2000;Weiderpass et al, 2000;Anderson et al, 2001;Sharma et al, 2001;Cook et al, 2006;Friberg et al, 2007). Overweight and obesity are major risk factors for both conditions since they are related to increased endogenous oestrogen levels (Parazzini et al, 1991;Calle et al, 2003;Cook et al, 2006).…”
mentioning
confidence: 99%
See 3 more Smart Citations